Launch of the Gregorian Journal of Health Sciences: a new horizon in scientific dissemination - Galarza, Judith (Revista Gregoriana de Ciencias de la Salud, 2024)
With great enthusiasm we present to you the first issue of the Gregorian Journal of Health Sciences, an initiative of the Medicine degree at the San Gregorio University of Portoviejo, Ecuador, which arose with the purpose of establishing a scientific communication platform specialized in the vast and dynamic field of Health Sciences. In this inaugural editorial, we want to share with you our perspective on the importance of scientific dissemination, the mission and vision that will guide our work, as well as provide you with an approach to the topics and articles that make up this initial issue.